Avifauna de duas áreas de Caatinga em diferentes estados de preservação no Raso da Catarina, Bahia - Nunes, Cristiane Estrêla Campodonio (2011)
The area of Caatinga covers a semiarid area with approximately 800,000 km ². In the northeast of Bahia, on the right bank of Rio São Francisco, located in the region of the Raso da Catarina, with approximately 390.000 ha. Within the region of Raso da Catarina, is the Estação Ecológica Raso da Catarina (EERC). We analyzed bird communities in two areas of caatinga Raso da Catarina, one inside the EERC (Area I) and another in the vicinity of this station (Area II), aiming to determine their riches, abundance and relative frequency of occurrence of its species, trophic groups, as well checking the occurrence of migratory species, endemic, threatened and indicator of environmental quality recording, too, their habitat use and its sensitivity to human disturbance. Four expeditions were conducted, ten days each month between september 2009 and may 2010. Obtaining and composition was performed by visual recording and/ or hearing, following the method lists Mackinnon. We recorded 156 species, 116 and 133 in Area I Area II, observed a similarity in the composition of birds between these two areas (0,61). In Area I there were more rare species, then by the regular species, uncommon and common in Area II were more rare species, then by uncommon species, common and regular. In both areas were the most common insectivorous species, then by omnivores. In Area I semidependent predominant species, then by the independent and dependent species of forest habitats, while in Area II were predominant independent species, then by species semidependent and dependents. Regarding the sensitivity of species to human disturbance, both Area I and Area II showed a predominance of species such as low sensitivity then by species with medium and high sensitivity. When analyzing the proportions of occurrence of trophic groups, species with dependence on forest environments and sensitive to human disturbance is possible to verify that the bird communities reflect the slightly different environmental conditions. In environments with different preservation state bird species tend to present a greater ecological flexibility.